Effects of Enzyme Addition on the Processing Characteristics of Frozen Dough and the Quality of the Steamed Bread - Hongwei WANG; Qinyue NIE; Jingyue QIAO; Yu ZHANG; Huishan SHEN; Xingli LIU; Xuewei ZHAO; Hua ZHANG; Yanyan ZHANG (Shipin gongye ke-ji)
Quality deterioration issues, such as insufficient gas retention, a rough taste, and a propensity to collapse, are usually encountered in frozen dough and its prepared flour products. To improve the fermentation characteristics and quality of frozen dough and its processed products, different levels of α-amylase preparations were added to frozen dough, and the optimal conditions affecting the specific volume of steamed bread made with the supplemented dough were determined. The fermentation characteristics of the enzyme-supplemented frozen dough, the quality of the steamed bread, and the structure of the dough starch were studied using a fermentation rheometer, rheometer, texture analyzer, and scanning electron microscope. The results showed that α-amylase was the most significant factor affecting the specific volume of steamed bread. Compared with the fermentation characteristics of dough subjected to a freeze-thaw cycle, a trend of first increasing and then decreasing was shown by those of the supplemented frozen dough with the increase in α-amylase level added, indicating that the fermentation rate and gas production capacity of frozen dough could be greatly improved by supplementation with an appropriate amount of α-amylase (90 mg/kg). The energy storage modulus (G') of the supplemented frozen dough showed an increasing trend, indicating that the proper amount of enzyme preparation added facilitated the formation and stability of the gluten network. The specific volume, hardness, and sensory scores of steamed bread made with the enzyme-supplemented frozen flour improved significantly, with the hardness decreasing from 985.24 to 555.86 g and the specific volume increasing from 1.89 to 2.26 mL/g. Additionally, the changes in the starch structure of frozen dough before and after the addition of enzyme were analyzed, and it was revealed that the starch particles in the supplemented dough were decreased in size and appeared concave or cracked, and the starch crystalline structure was observed to first increase and then decrease. These results indicated that the fermentation characteristics of dough and the quality properties of steamed bread could be improved by the enzyme preparation through influencing the starch microstructure.